2012
DOI: 10.1371/journal.pone.0037788
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Carbapenem-Resistant Acinetobacter baumannii Infection in Acute Care Hospitals in Taiwan: Association with Hospital Antimicrobial Usage

Abstract: ObjectiveCarbapenem-resistant Acinetobacter baumannii (CRAB) has emerged as an important pathogen causing healthcare-associated infections (HAIs) in Taiwan. The present study is aimed to investigate the epidemiology of HAIs caused by CRAB and the association of CRAB infection and hospital usage of different antimicrobials.MethodsTwo nationwide databases in the period 2003 to 2008, the Taiwan Nosocomial Infection Surveillance System and National Health Insurance claim data, were used for analysis. A total of 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
5
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 28 publications
2
36
5
2
Order By: Relevance
“…High MRSA in the present study partially may be due to less sample size as compared to the above study. The present study had no isolation of Vancomycin resistant Enterococci, Carbapenem resistant Acinetobacter or Clostridium difficile unlike a study by Morgan DJ et al [6] [7]. These students are potential sources for infection spread in health care settings which needs addressing specially by infection control committee.…”
Section: Discussioncontrasting
confidence: 50%
“…High MRSA in the present study partially may be due to less sample size as compared to the above study. The present study had no isolation of Vancomycin resistant Enterococci, Carbapenem resistant Acinetobacter or Clostridium difficile unlike a study by Morgan DJ et al [6] [7]. These students are potential sources for infection spread in health care settings which needs addressing specially by infection control committee.…”
Section: Discussioncontrasting
confidence: 50%
“…Previous studies used individual-level data to investigate the association between antibiotic exposure and acquisition of resistance, and few studies have investigated aggregated population-level data [12][13][14]. Aggregated population-level data may be more suitable for such investigations because they consider the exposure of an entire population [15,16]. This study was conducted in order to investigate antibacterial consumption levels and specific patterns using the standardized ATC/DDD methodology.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that 11% of nosocomial isolates of A. baumannii were carbapenem-resistant; resulting in a morbidity and mortality rate of 52% as compared with a rate of 19% of patients infected with carbapenem-sensitive isolates (4,(11)(12)(13). Among the many carbapenem derivatives, imipenem initially was highly effective in the treatment of patients with A. baumannii infections; however, imipenem resistance has been confirmed in 53.7% of Acinetobacter nosocomial infections since the early 1990s (4,14,15). The most common pathways leading to carbapenem resistance are associated with the loss of outer membrane porins, overexpression of efflux pumps, and overproduction of Ambler class B metallo-␤-lactamases, class D oxacillinases, and AmpC cephalosporinase (16 -18).…”
mentioning
confidence: 99%